HUMAN RESILIENCE IN STOICISM: A LITERATURE REVIEW OF EPICTETUS AND MARCUS AURELIUS - Lisa Ayuniar (Academic Solution Publisher, 2025)
This study seeks to provide an explanation related to the concept of human resilience from the perspective of Stoicism as proposed by Epictetus and Marcus Aurelius. In the modern era, which is full of burdens and uncertainty, understanding resilience is very important. Using a literature study method, this review examines various journals related to the Stoic philosophy of Epictetus and Marcus Aurelius. The results of this study indicate that, from a Stoic perspective, resilience relies on a person's ability to manage their inner response to external circumstances, understand the limits of self-control, and develop a wise and sensible attitude. Epictetus emphasizes It is important to distinguish between aspects that are within our control and aspects that are beyond our control as the foundation for achieving peace of mind. Meanwhile, Marcus Aurelius emphasizes the importance of reflection, accepting reality, and living in harmony with nature. In general, the ideas of both provide a solid philosophical foundation for cultivating human resilience, especially when facing mental pressure and problems in modern life.